Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1093/humrep/den232
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive experience of HIV-infected women living in Europe

Abstract: Our results suggest that these days knowledge of HIV infection neither influences the desire for children nor the decisions regarding pregnancy in HIV-infected women living in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
3
28
1
Order By: Relevance
“…A European study suggested that being HIV-infected neither influenced the desire for children, nor the decision to become pregnant (Fiore et al, 2008), which has been corroborated by our qualitative findings. It has been shown that a variety of biomedical, individual and sociocultural factors influence pregnancy decisionmaking for HIV-positive women (Kirshenbaum et al, 2004), availability of treatment certainly plays an important role (Cooper et al, 2009).…”
Section: Aids Care 923supporting
confidence: 86%
“…A European study suggested that being HIV-infected neither influenced the desire for children, nor the decision to become pregnant (Fiore et al, 2008), which has been corroborated by our qualitative findings. It has been shown that a variety of biomedical, individual and sociocultural factors influence pregnancy decisionmaking for HIV-positive women (Kirshenbaum et al, 2004), availability of treatment certainly plays an important role (Cooper et al, 2009).…”
Section: Aids Care 923supporting
confidence: 86%
“…Although the majority of women interviewed in this study reported only one partner in the previous 12 months, 31.6% of the sample reported 10 or more sex partners in their lives. This number far surpasses those published in other Brazilian studies conducted in the general population (10%) 8 and in women living with HIV (19%) 15 . Evidence indicates that lifetime number of sex partners increases with age and the resulting time of sexual exposure 33,34 , and that the increase in number of partners is associated with early sexual initiation 29 .…”
Section: Discussioncontrasting
confidence: 48%
“…Various studies have attempted to evaluate the impact of the diagnosis of HIV infection on women, particularly in relation to their reproductive decisions 11,12,13,14,15 . In Brazil, several surveys have been documented on sexual behavior in the general population, using different methodologies 8,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The reported reasons for wanting to have children were mainly related to the ideas of liking children, wanting to form a family and pleasing their partner. Among the reasons for not wanting children, HIV infection played a major role, but was not a definitive factor [12]. Few of them had disclosed their HIV infection to their social circle and in most cases, only to the partner or very close familiar circle.…”
Section: Discussionmentioning
confidence: 99%